Refractory Sexual Arousal Subsequent to Sacral Neuromodulation - Dani Zoorob; Amanda S. Deis; Kathryn Lindsay (Case Reports in Obstetrics and Gynecology)
Background. Sacral neuromodulation has become a widely used treatment for lower urinary tract symptom and dysfunction. It has been observed to benefit sexual function in the domains of arousal and desire. Studies have yet to report markedly increased arousal symptoms as an adverse effect. Case. We present the case of a 57-year-old woman who developed symptomatic persistent genital arousal following implantation of a neuromodulator. Despite device reprogramming, a trial of the device being shut off, and eventual device removal, she continued to have residual new-onset undesired genital hyper-arousal symptoms. Conclusion. Our patient demonstrated markedly increased and persistent arousal symptoms that may be the result of upregulated or alternative activation of sacral nerve pathways. While other case reports describe improvement in persistent genital arousal disorder symptoms through neuromodulation, no studies mention hyperarousal symptoms as an adverse side effect after sacral neuromodulator placement nor persistence despite removal of the implant.